Obesity Effect on Induction of Labor Duration [25R]. (May 2017) - Fitzgerald, Garrett; Crimmins, Sarah; Kopelman, Jerome; Harman, Chris; Turan, Ozhan
Abstract : INTRODUCTION: Obesity and associated morbidity significantly impacts obstetric management, including increased indication for induction of labor (IOL). Retrospective studies report obesity prolonging labor course. We aim to investigate duration of IOL stratified by body mass index (BMI). We hypothesize obesity prolongs IOL. METHODS: Prospective cohort study of singletons undergoing IOL. Obstetric management was per provider's discretion (vaginal misoprostol, cervical balloon, intravenous oxytocin). The primary outcome was interval from starting IOL to latent labor. Secondary outcomes include duration to active labor and delivery. Labor was considered prolonged if greater than 24 h to latent labor, and greater than 36 h to active labor. Patients were analyzed by BMI category (under 30, between 30 and 39.9, over 40 kg/m 2 ). Cesarean delivery outcomes were excluded. Non-parametric and chi-square test were used for analysis. RESULTS: Total of 99 enrolled, 23 were delivered by cesarean, leaving 76 analyzed. The median BMI was 36 kg/m 2 (19-75); 17 BMI under 30, 37 BMI between 30 and 39.9, 22 BMI over 40. The parity and Bishop's score were not significantly different. The BMI group median duration to latent labor (10.6 v 9.6 v 12.7 h, P=.5), to active labor (14.1 v 15.0 v 19.2 h, P=.5), and to delivery (18.5 v 17.8 v 20.6 h, P=.5) were not significantly different. The time to achieve active labor trended longer with increasing BMI (P=.049). CONCLUSION: Prospectively analyzed induced labor curves were not significantly different between normal weight, obese, and severely obese women. This provides evidence that, regardless of BMI, IOL is a viable management option.